2016
DOI: 10.1109/tpwrs.2015.2454517
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-Based Monitoring of Multiple Outages With PMU Measurements of Area Angle

Abstract: When power grids are heavily stressed with a bulk power transfer, it is useful to have a fast indication of the increased stress when multiple line outages occur. Reducing the bulk power transfer when the outages are severe could forestall further cascading of the outages. We show that synchrophasor measurements of voltage angles at all the area tie lines can be used to indicate the severity of multiple outages. These synchrophasor measurements are readily combined into an "area angle" that can quickly track t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…However, there are some exceptional cases in which the area angle does not respond inversely to the maximum power transfer. These exceptional cases usually correspond to local power redistribution problems as explained in (10) and further in Chapter 3 of this thesis. Depending on the nature of the lack of response, some of the lines giving exceptional outages need to be independently monitored to improve the accuracy of the interpretation of the area angle changes.…”
Section: Effect Of Exceptional Outagesmentioning
confidence: 97%
See 4 more Smart Citations
“…However, there are some exceptional cases in which the area angle does not respond inversely to the maximum power transfer. These exceptional cases usually correspond to local power redistribution problems as explained in (10) and further in Chapter 3 of this thesis. Depending on the nature of the lack of response, some of the lines giving exceptional outages need to be independently monitored to improve the accuracy of the interpretation of the area angle changes.…”
Section: Effect Of Exceptional Outagesmentioning
confidence: 97%
“…Previous work uses area angle to define thresholds to monitor stress across the area under various contingencies (10) and showed that area angle is a good indicator of stress. The strategy is to define thresholds based on the line limits in terms of maximum power transfer through the area and convert the maximum power transfer threshold to an equivalent area angle threshold to monitor stress across the area.…”
Section: Evaluating the Maximum Power That Can Enter An Area Under Simentioning
confidence: 99%
See 3 more Smart Citations